Pengaruh Model PjBL Dengan Pendekatan Experiential learning Terhadap Kompetensi Siswa - Lubis, Citra Aulianisa; Chamisijatin, Lise; Zaenab, Siti (Journal of Natural Sciences, 2025)
This study aims to determine the influence and achievement of competency from the PjBL learning model with the Experiential learning approach. The research method used is quantitative Pre-experiment through the One Group Pretest-Posttest design approach. The study was conducted on students of class VIII IPA SMP Muhammadiyah 02 Batu City. The instruments used were pretest and posttest assessments. In data analysis using paired t-test. The results showed that the application of the PjBL model with the Experiential learning approach had a significant influence on learning outcomes (Sig = 0.001 0.05) and student competency achievement which can be seen based on increased learning outcomes, achievement of attitude values and skills. Overall, students also get memorable experiences during the learning stages of the PjBL learning model through the Experiential learning approach.